Herbal beverage packaging product design using kansei engineering - Kiki Pratiwi; Mohammad Taufan Andreyanto; Muhammad Asrol; Taufik (JENIUS : Jurnal Terapan Teknik Industri, 2023)
The appearance of the packaging on drinks is a required consumer attraction factor, because the appearance of herbal drinks will compete with manufactured beverage products. This article aims to identify consumer needs in the packaging design of the products, determine the design element in the herbal beverage packaging. This study discusses the design of herbal beverage packaging using the kansei engineering method. The kansei engineering method is a design method using the emotional approach of the respondents. The steps in solving using the kansei method are, the first step is to collect kansei words and structuring kansei words, the second is to determine the factors from the respondents' responses, the third is to calculate the relationship between the factors and the variables in it. The result of this research is to design a herbal beverage packaging that is adapted to the selected kansei words. Kansei words used as the basis for packaging design include practical, attractive, informative, quality packaging materials, colorful, medium packaging sizes, medium packaging forms, modern packaging forms, innovative, pictorial, recyclable, transparent packaging bottles, interesting writing fonts